The relevance of uncertainty and goal conflict to mental disorders, their prevention and management: a unifying approach. (6th December 2016) - Einstein, Danielle A.; Mansell, Warren
Abstract: Intolerance of Uncertainty (IU) has been shown to underlie a range of disorders. Technological advances have produced a decline in our development of an ability to wait in the face of uncertainty. The paper provides an update on empirical, theoretical and neural research in IU. Einstein's extended trandiagnostic model of IU is described. This model is based on control theory. The research update and IU model propose specific tools which can be implemented within transdiagnostic treatment approaches.